THE USE OF METAPHOR IN EDGAR ALLAN POE’S SHORT STORY THE BLACK CAT - Faizal Risdianto (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2014)
This study is aimed to elaborate the uniqueness of Edgar Allan Poe’s short story entitled The Black Cat. This research is a (qualitative) bibliographical study. The object of the study is the use of metaphor in Edgar Allan Poe’s short story The Black Cat. There are 21 sentences chosen to represent all the metaphorical sentences of Edgar Allan Poe being the object of the study. Having analyzed the data by the perspective of George Lakoff and Johnson’s conceptual metaphor, the researcher can draw a conclusion that Edgar Allan Poe has succesfully used effective and creative metaphorical expressions in depicting the psychological ambnormality of the main character in his short story. His remarkable metaphorical expression shows his distictive position as one of the greatest American man of letters. Keywords: Metaphor, Source Domain, Target Domain, and Short story.